2004
DOI: 10.1016/j.jtcvs.2003.08.048
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between computed tomographic findings, bronchioloalveolar carcinoma component, and biologic behavior of small-sized lung adenocarcinomas

Abstract: Small-sized adenocarcinomas with a greater ratio of bronchioloalveolar carcinoma component showed less aggressive behavior. Both tumor shadow disappearance rate and ground-glass opacity ratios, which are obtained preoperatively, were well associated with bronchioloalveolar carcinoma ratios, which are determined postoperatively. Furthermore, tumor shadow disappearance rate had a stronger impact as a predictor of bronchioloalveolar carcinoma component. Preoperative assessment of tumor shadow disappearance rate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
62
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 20 publications
6
62
0
Order By: Relevance
“…Okada showed that both TDR and GGO were well associated with BAC ratios (i.e., the fraction of the tumor that is GGO), which are determined postoperatively. The TDR also had a stronger impact as a predictor of the BAC component (26). The authors recommended calculating TDR because it is more objective than qualitatively evaluating the ratio of GGO, which can have high interobserver variability (27).…”
Section: Discussionmentioning
confidence: 99%
“…Okada showed that both TDR and GGO were well associated with BAC ratios (i.e., the fraction of the tumor that is GGO), which are determined postoperatively. The TDR also had a stronger impact as a predictor of the BAC component (26). The authors recommended calculating TDR because it is more objective than qualitatively evaluating the ratio of GGO, which can have high interobserver variability (27).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some recent investigators have begun to address the possibility of lung parenchymal sublobar limited resection for this specific subgroup of small lung cancers with GGO appearance [1][2][3][4][5][6][7]. Although operative procedures are generally dependent on size, number, and location of lesions, limited resection procedures, such as wedge resection, are a well-recognized form of operative procedure for small-sized pure GGO.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Components of BAC appear to present as areas of ground-glass opacity (GGO) on HRCT, defined as a hazy increase in lung attenuation without obscuring underlying vascular markings, 6 and they can also be expressed as areas of tumor shadow disappearance rate (TDR), defined as the ratio of tumor area of the mediastinal window to that of the lung window on HRCT. 7 Therefore, the GGO ratio or TDR might be linked to the grade of adenocarcinoma malignancy. 3,[7][8][9] However, a recent large phase 2 study demonstrated that preoperative radiographic findings on HRCT cannot accurately diagnose the pathological invasiveness of small lung adenocarcinoma.…”
mentioning
confidence: 99%
“…7 Therefore, the GGO ratio or TDR might be linked to the grade of adenocarcinoma malignancy. 3,[7][8][9] However, a recent large phase 2 study demonstrated that preoperative radiographic findings on HRCT cannot accurately diagnose the pathological invasiveness of small lung adenocarcinoma. 10 In contrast to anatomic images of CT, positron emission tomography (PET) with F18-fluorodeoxyglucose (FDG) quantitatively images glucose metabolism, which reflects the metabolic activity and proliferative potential of malignant tumors, and it is therefore widely and increasingly used for the diagnosis, staging, and therapeutic assessment of non-small cell lung cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation